Can an organizationally anchored, multilevel intervention improve perceived stress and psychosocial factors in the workplace? A pre-post study assessing effectiveness and implementation - Vita Ligaya Dalgaard; Tanja Kirkegaard; Christian Dyrlund Wåhlin-Jacobsen; Birgit Aust; Sofie Jaspers; Thomas Faurholt Jønsson; Trine Nøhr Winding (BMC Public Health)
Abstract Background Organizational multilevel interventions have been called for as a means to improve psychosocial working conditions, reduce stress, and enhance wellbeing in organizations. However, these types of interventions are highly complex to implement and evaluate, and they remain scarce in the literature. In this study, we present the evaluation of a multilevel intervention conducted in a municipality setting. Methods The intervention was based on a train-the-trainer principle and participatory risk assessment workshops on all organizational levels. Action plans were subsequently developed at the team level, and identified risks, which could not be addressed at the team level, were reported to the management for further action planning or escalation to the next management level. Using a pre-post study design, we evaluated changes in proximal outcomes related to the psychosocial working environment, and distal outcomes related to stress and job satisfaction. Changes over time in outcome measures were analyzed using linear mixed models. A quantitative process evaluation was used to examine the degree of implementation of the intervention. Results Small improvements over time were observed with regard to quantitative demands, overall perception of the psychosocial work environment, job satisfaction, and the psychosocial safety climate. We also observed an increase in empowering leadership. Positive tendencies were also found for predicatability at work, possibilities for solving work tasks and support from closest manager. The effect sizes were small in all cases. No improvements in perceived stress or stress symptoms were found. The study revealed several practical and methodological challenges in conducting and implementing this type of multilevel intervention in a municipal setting. Conclusions Overall, our study suggests that the intervention was associated with small positive changes in certain aspects of the working environment but no improvements were observed in stress outcomes. The study highlights a number of challenges in relation to implementing this type of multilevel intervention in a municipal setting. Trial Registration The study was prospectively registered at ISRCTN84940247 on April 23, 2019.